Needs assessment study for marketdriven agricultural technology transfer and commercialization in Abia State, Nigeria: RUSEP - Kormawa, P.M.; Kolawole, K.B; Azuogu, I.; Okorji, E.C.; Ezedinma, C.I. (2002)
RUSEP is the latest attempt by the federal government of Nigeria to alleviate poverty through the transfer of market-driven agricultural technology to farmers and the commercialization of agriculture in selected states in Nigeria. Through this project, employment will be generated through enhanced agricultural enterprises. Abia state in the southeast was chosen as one of the pilot states. The needs assessment study provides information on existing and available improved technologies and level of commercialization of agriculture in the rural communities. The constraints to commercialization and adoption of market-driven technologies were identified and recommendations were made towards the effective implementation of the project. The project will be useful in the implementation of the pilot project which has a lifespan of 18 months. Yam, cassava, rice and plantain were selected as priority major crops, taking into consideration their potential adaptability to commercial processing capability, socioeconomic and cultural significance, as well as their comparative advantage in terms of production and consumption in various processed forms. Yam and plantain flour were found to be the most profitable processed products for the study area. Plantain and cooking banana flour were new, emerging products with a high future market-driven potential. Similarly, certain criteria were also used to select the sites, namely Bende local government area (LGA) and Ukwa East or West LGA. Yam and rice are produced mostly in BendeLGA while plantain and cooking banana are produced in Ukwa east and West LGS. Although all the crops selected are widely grown with improved varieties, there would be an added value, if the farmers or group of farmers were able to process their produce. Consequently, emphasis is placed on processing in the report. Presently, gaps exist in the production of various agricultural technologies, such as in miniset seed yam, agrochemicals, and fertilizers. There is a weak amphasis on the dissemination of processing technologies; poor linkages exist between farmers and various stakeholders in the farming enterprise, there is policy instability and inadequate institutional support, as well as lack of market opportunities, and infrastructure, microcredit and credit support facilities.